2014
DOI: 10.3892/ijo.2014.2433
|View full text |Cite|
|
Sign up to set email alerts
|

Induction of antigen-specific cytotoxic T lymphocytes by fusion cells generated from allogeneic plasmacytoid dendritic and tumor cells

Abstract: Previous work has demonstrated that fusion cells generated from autologous monocyte-derived dendritic cells (MoDCs) and whole tumor cells induce efficient antigen-specific cytotoxic T lymphocytes. A major limitation to the use of this strategy is the availability of adequate amounts of autologous tumor cells. Moreover, MoDCs from cancer patients are often defective in their antigen-processing and presentation machinery. In this study, two types of allogeneic cells, a leukemia plasmacytoid dendritic cell (pDC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Whole ablated tumor cells might serve as general cancer antigens, and hyperthermia-induced exposure to the composition of whole tumor cells might be a superior alternative to other well-known antigen-loading vaccines [28]. This study provided the foundations for an effective and broadly applicable treatment to a wide range of cancer indications for which tumor-associated antigens have not been identified.…”
Section: Resultsmentioning
confidence: 99%
“…Whole ablated tumor cells might serve as general cancer antigens, and hyperthermia-induced exposure to the composition of whole tumor cells might be a superior alternative to other well-known antigen-loading vaccines [28]. This study provided the foundations for an effective and broadly applicable treatment to a wide range of cancer indications for which tumor-associated antigens have not been identified.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers administer the fusion between dendritic cells and whole tumor cells by chemical, physical, or viral means and generate hybrids that display both known and unidentified TAAs originally expressed by whole tumor cells. Then, the dendritic-tumor hybrids process multiple TAAs endogenously and present antigenic peptides to both major histocompatibility complex classes I and II molecules to activate both CD4 + and CD8 + T cells, thus activating the antitumor immunity [81, 82, 102, 103]. Dendritic–tumor cell fusion provides strategies to produce dendritic-tumor cell fusion-based tumor vaccines to display immunotherapy for tumors.…”
Section: Tumor–stromal Cell Fusionmentioning
confidence: 99%
“…DC-tumor FC vaccines with fully allogeneic components have been demonstrated to induce clinical responses [ 45 ]. Moreover, we have shown that fusion cells generated with an allogeneic DC line and allogeneic tumor cell line can induce antigen-specific CTL responses in vitro [ 46 ]. These findings introduce the possibility of using defined allogeneic DCs and allogeneic tumor lines to induce antigen-specific CTLs for adoptive immunotherapy.…”
Section: Introductionmentioning
confidence: 99%